Enamel maturation: a brief background with implications for some enamel dysplasias - Robinson, Colin (Frontiers in Physiology, 2014)
The maturation stage of enamel development begins once the final tissue thickness has been laid down. Maturation includes an initial transitional pre-stage during which morphology and function of the enamel organ cells change. When this is complete, maturation proper begins. Fully functional maturation stage cells are concerned with final proteolytic degradation and removal of secretory matrix components which are replaced by tissue fluid. Crystals, initiated during the secretory stage, then grow replacing the tissue fluid. Crystals grow in both width and thickness until crystals abut each other occupying most of the tissue volume i.e. full maturation. If this is not complete at eruption, a further post eruptive maturation can occur via mineral ions from the saliva. During maturation calcium and phosphate enter the tissue to facilitate crystal growth. Whether transport is entirely active or not is unclear. Ion transport is also not unidirectional and phosphate, for example, can diffuse out again especially during transition and early maturation. Fluoride and magnesium, selectively taken up at this stage can also diffuse both in an out of the tissue. Crystal growth can be compromised by excessive fluoride and by ingress of other exogenous molecules such as albumin and tetracycline. This may be exacerbated by the relatively long duration of this stage, 10 days or so in a rat incisor and up to several years in human teeth rendering this stage particularly vulnerable to ingress of foreign materials, incompletely mature enamel being the result.